Advocacy Strategies of Civil Society Organisations in Decentralised Indonesia: an Exploration Using a Policy Window Framework - Irawan Irawan (UIN Sunan Gunung Djati, 2023)
This article examines the advocacy strategies employed by civil society organizations (CSOs) within the framework of decentralized governance. Using the policy window framework and the concept of an opportunity stream, the analysis investigates the extent to which decentralized governance influences the strategies adopted by CSOs. The research was conducted in Indonesia, a newly democratized developing country, and focused on two case studies involving local government efforts to improve public services with the goal of poverty alleviation, as part of the country's bureaucratic reform initiatives. This article addresses two key research questions: What strategies did CSOs employ to seize opportunities for advocating policy changes, and how has decentralized governance impacted CSOs? The findings indicate that CSOs utilized a strategy that involved opening political, problem, and policy windows, which included elements of decentralized governance and bureaucratic reform, as well as challenges related to citizens' ability to voice complaints about poor services and resistance from local governments regarding reform efforts. The article contributes to the literature on decentralized governance and policy windows, offering insights into lessons learned and potential areas for future research